PEMANFAATAN CLAY EX. BENGALON SEBAGAI AGREGAT BUATAN DAN PASIR EX. PALU DALAM CAMPURAN BETON DENGAN METODE STANDAR NASIONAL INDONESIA 03-2847-2002 - ADI PRAYOGA, BIMA (KURVA S JURNAL MAHASISWA, 2014)
This study used a mixed design of the Standar Nasional Indonesia 03-2847- 2002. Were performed in the laboratory using artificial coarse aggregate maximum size is the size of the coarse aggregate artificial 10-40 mm. The sample used for the maximum size of coarse aggregate artificial amounted to 30 samples. The results of the overall test that the clay ex. Bengalon have a fairly high abrasion value is 60.08% in aggregate categories that can not be used as coarse aggregate for concrete structural class II and quality of K-125, K-175 and K-225 with abrasion condition (27-40%) , a very high absorption values ranged 20.223% that control water demand in the concrete mix is relatively difficult, and low yields an average compressive strength of 28 days produced by the method SNI 03-2847-2002 for coarse aggregate maximum ukaran 10-40 mm ie 10 097 MPa compressive strength of the targeted (f'cr) = 25.7 MPa.